A review on bioconversion of paddy husk into biodiesel / Nur Aqilah Daud - Daud, Nur Aqilah (Faculty of Plantation and Agrotechnology, 2017)
Biofuel production can be categorized into biodiesel and bioethanol. Biodiesel is one alternative for transport fuel substitution. Rice husk is one of the most commonly available lignocellulosic material that can be converted to different type of fuels through a variety thermochemical conversion process. The application of bioconversion process which can convert rice husk into biodiesel is an advance technology to biodiesel that can reduce the pollution and costing problem. This review gives an overview of the method of treatment to produce rice husk into biodiesel.